Hepatic mTORC1 Opposes Impaired Insulin Action to Control Mitochondrial Metabolism in Obesity - Blanka Kucejova; Joao Duarte; Santhosh Satapati; Xiaorong Fu; Olga Ilkayeva; Christopher B. Newgard; James Brugarolas; Shawn C. Burgess (Cell Reports, 2016)
Dysregulated mitochondrial metabolism during hepatic insulin resistance may contribute to pathophysiologies ranging from elevated glucose production to hepatocellular oxidative stress and inflammation. Given that obesity impairs insulin action but paradoxically activates mTORC1, we tested whether insulin action and mammalian target of rapamycin complex 1 (mTORC1) contribute to altered in vivo hepatic mitochondrial metabolism. Loss of hepatic insulin action for 2 weeks caused increased gluconeogenesis, mitochondrial anaplerosis, tricarboxylic acid (TCA) cycle oxidation, and ketogenesis. However, activation of mTORC1, induced by the loss of hepatic Tsc1, suppressed these fluxes. Only glycogen synthesis was impaired by both loss of insulin receptor and mTORC1 activation. Mice with a double knockout of the insulin receptor and Tsc1 had larger livers, hyperglycemia, severely impaired glycogen storage, and suppressed ketogenesis, as compared to those with loss of the liver insulin receptor alone. Thus, activation of hepatic mTORC1 opposes the catabolic effects of impaired insulin action under some nutritional states.